The promise of Immuno-oncology: implications for defining the value of cancer treatment. - Kaufman, Howard L.; Atkins, Michael B.; Subedi, Prasun.; Wu, James.; Chambers, James.; Joseph Mattingly, T..; Campbell, Jonathan D.; Allen, Jeff.; Ferris, Andrea E.; Schilsky, Richard L.; Danielson, Daniel.; Lichtenfeld, J. Leonard.; House, Linda.; Selig, Wendy K. (Tufts University. Tisch Library., 2019)
Abstract: The rapid development of immuno-oncology (I-O) therapies for multiple types of cancer has transformed the cancer treatment landscape and brightened the long-term outlook for many patients with advanced cancer. Responding to ongoing efforts to generate value assessments for novel therapies, multiple stakeholders have been considering the question of "What makes I-O transformative?" Evaluating the distinct features and attributes of these therapies, and better characterizing how patients experience them, will inform such assessments. This paper defines ways in which treatment with I-O is different from other therapies. It also proposes key aspects and attributes of I-O therapies that should be considered in any assessment of their value and seeks to address evidence gaps in existing value frameworks given the unique properties of patient outcomes with I-O therapy. The paper concludes with a "data needs catalogue" (DNC) predicated on the belief that multiple key, unique elements that are necessary to fully characterize the value of I-O therapies are not routinely or robustly measured in current clinical practice or reimbursement databases and are infrequently captured in existing research studies. A better characterization of the benefit of I-O treatment will allow a more thorough assessment of its benefits and provide a template for the design and prioritization of future clinical trials and a roadmap for healthcare insurers to optimize coverage for patients with cancers eligible for I-O therapy.; Keywords: Immunotherapy, Immuno-oncology, Value, Patient experience, Patient reported outcomes (PROs).; Springer Open.